PULMONARY VASCULAR WALL PARAMETERS IN EXPERIMENTAL DIABETES MELLITUS - Sobirova D. R. (Innovate Conferences, 2025)
Studying the morphofunctional state of pulmonary vascular endothelium in the alloxan diabetes model as a key aspect in evaluating the impact of diabetes on the pulmonary circulatory systemThe study analyzed the morphometric changes in small and medium-diameter pulmonary blood vessels. It was found that alloxan diabetes leads to thickening of pulmonary capillary walls, narrowing of vessel diameters, and endothelial damage. These pathological processes are primarily associated with endothelial dysfunction, cellular degeneration, and the toxic effects of glucose.
Keywords: Alloxan diabetes, pulmonary blood vessels, morphometry, endothelial dysfunction, microcirculation.